Studies on the biased signalling of some novel delta opioid receptor agonists - Asghar, Muhammad Junaid (2017)
The delta opioid receptor (DOR) is a G protein-coupled receptor (GPCR) which is important in the regulation of neuronal function, predominantly via coupling to heterotrimeric Gi/0 proteins. The receptor has been shown to be a potential target for the treatment of chronic pain and affective disorders. Although a large number of opioid agonists exist, their properties vary widely, at least partly due to their differential coupling to post-receptor signalling systems, a phenomenon referred to as ligand-biased signalling or functional selectivity.